Assessment of Butterflies in a Montane Temperate forest of Allain-duhaingan Catchment in Kullu, Himachal Pradesh, India - Proposed Hydroelectric Project Site - Bhardwaj, Manish; Uniyal, V. P. (Indian Forester, 2009)
40 species of butterflies, under 26 genera and 5 families were recorded from four habitat types of Allain-Duhaingan (streams) catchment, where a hydroelectric power station is proposed. Results from diversity indices and ANOVA showed that the butterfly species richness (F = 4.06, P = 0.001) and abundance (F = 2.71, P = 0.003) varied in different habitats. Species richness and abundance was higher along disturbed habitat (logging, project activities etc.) while, rarity was restricted to the most undisturbed habitats of the study area.